2020
DOI: 10.1186/s13034-020-00349-z
|View full text |Cite
|
Sign up to set email alerts
|

“I feel good when I drink”—detecting childhood-onset alcohol abuse and dependence in a Ugandan community trial cohort

Abstract: Background Alcohol, substance use, and mental health disorders constitute major public health issues worldwide, including in low income and lower middle-income countries, and early initiation of use is an important predictor for developing substance use disorders in later life. This study reports on the existence of childhood alcohol abuse and dependence in a sub-study of a trial cohort in Eastern Uganda. Methods The project SeeTheChild—Mental Child Health in Uganda (STC) included a sub-study of the Ugandan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…11 In 2014, we identified a prevalence of 8.4% clinically defined harmful alcohol use or dependence in a sample of children aged 5–8 years (n=119) with a high mental health symptom load. 12 This prompted further qualitative investigation, which corroborated our finding.…”
Section: Introductionsupporting
confidence: 86%
“…11 In 2014, we identified a prevalence of 8.4% clinically defined harmful alcohol use or dependence in a sample of children aged 5–8 years (n=119) with a high mental health symptom load. 12 This prompted further qualitative investigation, which corroborated our finding.…”
Section: Introductionsupporting
confidence: 86%
“…In the aforementioned English birth cohort, drinking at age 10 had a weaker association with conduct problems compared with depression, but the relationship was stronger in adjusted analysis 26. In a small study from Uganda (n=148), 10 out of the 11 children aged 5–8 years diagnosed with harmful alcohol use and dependence had psychiatric comorbidities, including conduct disorder, suicidality, panic disorder and depression 24. In a study from the USA, investigating suicidal ideation among more than a thousand 8-year-olds at risk for or victims of maltreatment, 21% had used substances, including alcohol.…”
Section: Determinants Of Early Alcohol Usementioning
confidence: 95%
“…26 In a small study from Uganda (n=148), 10 out of the 11 children aged 5-8 years diagnosed with harmful alcohol use and dependence had psychiatric comorbidities, including conduct disorder, suicidality, panic disorder and depression. 24 In a study from the USA, investigating suicidal ideation among more than a thousand 8-year-olds at risk for or victims of maltreatment, 21% had used substances, including alcohol. Further, children that used substances were four times more likely to report suicidal ideation, and this association was stronger among maltreated children.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…With about half of its population (49.3%) under the age of 15 years [ 3 ], Uganda is home to one of the world’s largest populations of children. Studies have detected alcohol consumption by children in Uganda, with some starting as young as 5 to 8 years old [ 4 6 ]. In addition, we found that primary school-age children in Mbale district, Uganda, reported easy access to alcohol, consuming it in various settings, including their homes, schools, and even classrooms during instructional sessions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%